Anatomical and visual outcomes of phacoemulsification and 23-gauge pars plana vitrectomy assisted with perfluorocarbon and 27-gauge twin-chandelier endoillumination for primary rhegmatogenous retinal detachment - Soon Wai Ch′ng; Patel Gordon-Bennett; Guzaliya Safiullina; Partha Ray Chaudhuri (Journal of Clinical Ophthalmology and Research, 2018)
Context: Anatomical and visual outcomes of phacoemulsification and 23-gauge (23G) pars plana vitrectomy (PPV) assisted with perfluorocarbon liquid (PFCL) and 27-gauge twin-chandelier endoillumination for primary rhegmatogenous retinal detachment (RRD). Aims: This study aims to determine the anatomical and visual outcomes of phacoemulsification and 23G PPV for primary RRD assisted with 27-gauge (27G) transconjunctival twin-chandelier endoillumination and bimanual vitreous base shaving under PFCL. Settings and Design: A prospective single tertiary center cohort study of 65 consecutive eyes by a single surgeon between August 2013 and June 2014. Subjects and Methods: The primary outcome measure was the primary retinal reattachment rate. The secondary outcome measure was best-corrected visual acuity (BCVA). All patients were reviewed postoperatively up to 4 months. Statistical Analysis Used: Chi-squared, Student's t-test, and one-way ANOVA test were used in this study. Results: At 4 months, overall retinal reattachment was 83.1% with a single operation and 87.7% with a second surgery. After exclusion of the proliferative vitreoretinopathy (PVR) cases, the primary retinal reattachment rate improved to 93.9% and secondary retinal reattachment rate was 98.0%. The mean BCVA improved from logMAR 1.06–0.83 (P = 0.002). PVR (P = 0.0001), silicone oil tamponade (P = 0.002), macula-off RD (P = 0.12), location of RRD (P = 0.09), and delay of more than 7 days for surgery (P = 0.09) were associated with a higher redetachment rate. The main postoperative complications were small bubbles of PFCL in the posterior segment (18.5%) and subretinal PFCL (3.1%). Conclusions: Chandelier endoillumination and PFCL-assisted 23G PPV with phacoemulsification has reattachment rates and visual outcomes similar to the current standard of RRD repair of different complexities. This surgical technique can be considered an alternative method of repairing RRD, with some advantages.